Implementasi Pengalaman Panca Indra pada Interior Restoran Bentoya di Surabaya - Livia Stefany (Intra, 2017)
The sense of vision commonly plays the most dominant role in interior, such as color, material, shape, lighting, and others. However other senses such as smell, auditory, haptic are typically less considered. Without the design of non-visual sensory, customers’ could not feel maximum experience. This is due to non-visual sensory sensation that enhances visual perception of customers. The aim of this study is to understand the importance of the role of the senses as one of the instruments to experience space. The method used is the qualitative descriptive method based on the theory of Joy Monice Malnar and adopts the case study of Bentoya restaurants that are located in 5 malls throughout Surabaya. According to the analysis, it can be concluded that the experience of senses plays a prominent role for humans to experience space. Overall, there are various experiences that involve many of the senses in the interior of Bentoya restaurant. Customers go through various experiences through the implementation of distinctive Japanese elements in every Bentoya restaurant, starting from the floors, walls, ceiling, until the decorative elements. Haptic in theory is referred as the most influential sense in experiencing space, which is evident in the case study with various experience that could be felt by the body, be it directly or beginning with the other senses first. For example, the elements of wood and bamboo can be experienced through visual, auditory and haptic senses.